Evaluación de cuatro técnicas quirúrgicas de orquiectomía en machos caninos (canis familiaris). - Álvarez Álvarez, Maria Jose (2016)
Four surgical techniques (open-scrotal slitting, cut scrotal with coronary closed, open and pre scrotal perianal open) of orchiectomy in dogs were evaluated at the veterinary clinic "Miller" Chone located in the parish Chone, Canton Chone. The type of work was experimental, in which the observation technique was used and verified daily development of each treatment. A completely randomized design was applied so the experiment was worked with 5 dogs per treatment (20 in total) of mixed race up to 3 years old was used. The variables measured were: healing time, weight loss post castration, presence of bloody exudates, cost benefit. Once the investigation started it was found that the fifth day (120 H) 80% of patients treated with perianal surgical technique had a higher wound healing, unlike the 20% reflected in the scrotal technique with coronary cut, the rest of other techniques’ wound even the remaining non-healed. Only neutered dogs only with pre scrotal technique obtained 4 g weight loss. Neutered dogs with pre scrotal technique showed a higher presence of exudate (19, 60 cm), neutered dogs with perianal technique obtained a smaller presence of exudate (9.40 cm). The lower costs were obtained with open-scrotal slitting, and cut scrotal with coronary closed with $ 30.93 for each of them, the pre scrotal perianal open technique in spite of being the largest economic cost turned out be the most beneficial for animal welfare.